The Nazification and Denazification of the University of Göttingen - Ericksen, Robert P. (The betrayal of the humanities, 2022)
Robert P. Ericksen begins with the widespread view that German universities in the late-nineteenth and early twentieth centuries were the best in the world. He then adds the assumption that this might have made them a natural place to question and criticize the anti-humanistic Nazi ideology and the poorly-educated Adolf Hitler. However, even before Hitler’s rise to power in 1933, universities were subject to antisemitic prejudice and angry nationalism. Furthermore, among the student population, enthusiastic Nazis had managed to take over student government. Already by 1931, they had weaponized their antisemitism and hyper-nationalism with boycotts and demonstrations. Hitler’s actual rise to power led to a dramatic purge of Jewish and leftwing professors beginning in April and a day for celebratory book-burning in May. Professors accepted and even supported these events, sacrificing their supposed academic ideals for a “political university” in support of the Nazi cause. Ericksen employs his research into postwar denazification at Göttingen University to describe the betrayal of that university’s academic values during the Nazi era, and also to reflect upon the difficulties of transition after 1945.